Vatellini Sharp (Coleoptera, Dytiscidae) from Brazil: two new species, new records, and a checklist - Braga, Rafael Benzi; Ferreira-Jr, Nelson (Zootaxa, 2016)
The tribe Vatellini Sharp, 1882 is composed of 55 species divided in two genera. Even though a recent revision of the tribe was made, Vatellini of the new world are weakly explored with great gaps in the distributions of species. In Brazil the knowledge is based only on a few localities. In this work two new species are described and illustrated, Vatellus caissara sp. nov. and Vatellus yanomami sp. nov.; new records are given for Brazil: Vatellus maculosus Miller, 2005 in the state of Mato Grosso, Derovatellus lentus (Wehncke, 1876) in Amazonas, Pará and Rio de Janeiro, Vatellus lateralis (Sharp, 1882) in Alagoas, Ceará, Espírito Santo, Pará, Pernambuco and Rio Grande do Sul, Vatellus sahlbergi (Sharp, 1882) in Rio de Janeiro, and Vatellus tarsatus (Laporte, 1835) in Pará. A checklist with all species of Vatellini occurring in Brazil is provided and steps for identification of the new species are added in the key of Miller (2005).